Saliva in studies of epidemiology of human disease: the UK Biobank project. Issue 1 (February 2016) - Galloway, John W.; Keijser, Bart J. F.; Williams, David M.
Abstract: There has been immense interest in the uses of saliva in the diagnosis of systemic disease over the past decade and longer because it is recognized that saliva possesses great potential as a diagnostic fluid. In spite of this, the usefulness of saliva in studies of the epidemiology of human disease has still to be properly evaluated. This review describes the UK Biobank project and explores the scope to use this and other such cohort studies to gain important insights into the epidemiological aspects of systemic disease. The Biobank holds around 85, 000 well‐characterized saliva samples, together with blood and urine samples, the results of a battery of physiological tests, a full medical history and a detailed description of the subject's lifestyle. This repository is a resource for insightful and highly powered oral and dental research.